2020
DOI: 10.1371/journal.pone.0242497
|View full text |Cite
|
Sign up to set email alerts
|

Renin angiotensin system genes are biomarkers for personalized treatment of acute myeloid leukemia with Doxorubicin as well as etoposide

Abstract: Despite the availability of various treatment protocols, response to therapy in patients with Acute Myeloid Leukemia (AML) remains largely unpredictable. Transcriptomic profiling studies have thus far revealed the presence of molecular subtypes of AML that are not accounted for by standard clinical parameters or by routinely used biomarkers. Such molecular subtypes of AML are predicted to vary in response to chemotherapy or targeted therapy. The Renin-Angiotensin System (RAS) is an important group of proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Seyhan et al showed that RAS genes and identified their association with doxorubicin and etoposide sensitivity. They also found that GF2R, CTSA, and ATP6AP2 were gene biomarkers, which can subgroup AML patients into distinct good and bad prognostic groups (24). We try to find more drug-sensitive biomarker genes for AML-ETO patients and improve AML patient efficiency.…”
Section: Discussionmentioning
confidence: 96%
“…Seyhan et al showed that RAS genes and identified their association with doxorubicin and etoposide sensitivity. They also found that GF2R, CTSA, and ATP6AP2 were gene biomarkers, which can subgroup AML patients into distinct good and bad prognostic groups (24). We try to find more drug-sensitive biomarker genes for AML-ETO patients and improve AML patient efficiency.…”
Section: Discussionmentioning
confidence: 96%
“…These findings about dyslipidemia suggest that the blood lipid profile of patients with leukemia may be a diagnostic/ prognostic factor in the treatment of acute leukemia. In the exploration of leukemia resistance to chemotherapy, some studies have found that renin-angiotensin system (RAS) gene can divide AML patients into different subtypes, and may also be a biomarker of AML drug sensitivity and prognosis (Turk et al, 2020). Excitingly, it has been reported that inhibition of RAS remodels the triacylglycerol network (Sas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The development of multidrug resistance (MDR) involves multiple mechanisms [ 5 ], which are ATP-binding cassette (ABC) overexpression-induced drug efflux pumps that reduce intracellular drug concentrations [ 6 ], FLT3 mutation [ 7 ], DNA repair abnormalities [ 8 ], apoptosis tolerance [ 5 ], and bone marrow microenvironment changes [ 9 ]. Doxorubicin (ADM) is a first-line chemotherapeutic drug used in AML [ 10 ] and has been recorded to mediate caspase activation and apoptotic DNA fragmentation to induce death of AML cells [ 11 ]. Resistance to ADM involves upregulation of proteins from the ABC superfamily to cause efflux of the drug in AML cells [ 12 ], which remains a significant obstacle to the successful treatment of AML.…”
Section: Introductionmentioning
confidence: 99%